Risk Factors and Adverse Events During Intra Hospital Transportation Among Critically Ill with a View to Develop Patient Transport Checklist (International Journal of Nursing Education, 2022)
AIM: A study to assess the risk factors and adverse events during intra hospital transportation among critically ill with a view to develop patient transport checklistOBJECTIVES:1.To determine the risk factors associated with intra hospital transportation of critically ill patients.2.To identify the adverse events that occurs during intra hospital transport of critically ill patients.3.To correlate the risk factors of intra hospital patient transportation and selected baseline variables.4.To find out the association between risk factors during intra hospital transport and selected baseline variables5.To develop an intra-hospital patient transport checklistMETHODOLOGY: For this study, a descriptive research design was used and 100 critically ill patients were selected using convenient sampling technique. Baseline variables, were assessed using baseline proforma, risk factors and adverse events were identified by using the checklists. Formal written permission was obtained from the authorities prior to the data collection process. The data was analyzed by using both descriptive and inferential statistics on the basis of objectives and assumptions of the study.RESULT: Positive correlation was found between the patients risk score of transportation with APACHE II (rs= 0.48) and FiO2(rs=0.58). APACHE II (p=0.001), GCS (p=0.001), heart rate during transport (p=0.007), MAP during transport (p=0.010),respiratory rate during transport (p=0.031), Fio2 during transport (p=0.001), airway (Z= -7.03,p =0.001), mode of transport (Z= -3.08, p=0.002), presence of central venous lines(Z= -7.08,p=0.001), arterial line (Z= -3.79,p=0.001), ionotropes (Z= -5.08,p=0.001), sedation(Z= -3.11 p=0.002), nasogastric tube (Z= -7.62, p=0.001) and Foleys catheter (Z= -4.55, p=0.001) have significant association with patients risk scores of transportation. Hence, the researcher concludes that identifying the patients risk scores before transportation can significantly reduce the adverse events during transport by strict adherence to hospital protocols and usage of checklists.
Keywords: Adverse events, Intra hospital transportation, Risk factors.